Superintelligence [videorecording (DVD)] - McCarthy, Melissa, 1969-; Smart, Jean; Corden, James (Warner Bros. Entertainment Inc., 2022)
Nothing extraordinary ever happens to Carol Peters, so when she starts getting snarky backtalk from her TV, phone, and microwave, she thinks she's being punked. Or losing her mind. The world's first superintelligence has chosen to study and observe Carol's attempt to romantically reconcile with her former boyfriend to better understand the human condition. Soon, the all-powerful entity takes over her life ... with ominous plans to possibly take over the world. Now, Carol is potentially humanity's last chance before this AI-with-an-attitude decides to pull the plug.